FoxM1 overexpression promotes epithelial-mesenchymal transition and metastasis of hepatocellular carcinoma - Meng, Fan-Di (World J Gastroenterol, 2015)
AIM: To investigate the expression of forkhead box protein M1 (FoxM1) in the process of epithelial mesenchymal transition in hepatocellular carcinoma (HCC) and its role in metastasis. METHODS: FoxM1 and E-cadherin expression in HCC tissue microarray specimens was evaluated by immunohistochemical staining, and statistical methods were applied to analyze the correlation between FoxM1 and epithelial-mesenchymal transition (EMT). Kaplan-Meier analysis of the correlation between the FoxM1 expression level and recurrence or overall survival of HCC patients was performed. The expression of FoxM1, E-cadherin and snail homologue 1 (SNAI1) in HCC cell lines was evaluated by real-time reverse transcription-polymerase chain reaction and Western blot. Hepatocyte growth factor (HGF) was used to induce EMT and stimulate cell migration in HCC cells. The expression of FoxM1 and SNAI1 was regulated by transfection with plasmids pcDNA3.1 and siRNAs in vitro. The occurrence of EMT was evaluated by Transwell assay, morphologic analysis and detection of the expression of EMT markers (E-cadherin and vimentin). Luciferase and chromatin immunoprecipitation assays were used to evaluate whether SNAI1 is a direct transcriptional target of FoxM1. RESULTS: FoxM1 expression was increased significantly in HCC compared with para-carcinoma (10.7 ± 0.9 vs 8.2 ± 0.7, P < 0.05) and normal hepatic (10.7 ± 0.9 vs 2.7 ± 0.4, P < 0.05) tissues. Overexpression of FoxM1 was correlated with HCC tumor size, tumor number, macrovascular invasion and higher TNM stage, but was negatively correlated with E-cadherin expression in microarray specimens and in cell lines. FoxM1 overexpression was correlated significantly with HCC metastasis and EMT. In vitro, we found that FoxM1 plays a key role in HGF-induced EMT, and overexpression of FoxM1 could suppress E-cadherin expression and induce EMT changes, which were associated with increased HCC cell invasiveness. Next, we confirmed that FOXM1 directly binds to and activates the SNAI1 promoter, and we identified SNAI1 as a direct transcriptional target of FOXM1. Moreover, inhibiting the expression of SNAI1 significantly inhibited FoxM1-mediated EMT. CONCLUSION: FoxM1 overexpression promotes EMT and metastasis of HCC, and SNAI1 plays a critical role in FoxM1-mediated EMT.